The Training Needs Analysis (TNA) as a Strategy for Competency Development and Employee Performance Improvement (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2026)
This study aims to analyze the Training Needs Analysis (TNA) process as a strategy for developing employee competency and improving performance among lecturers at Politeknik Pajajaran Insan Cinta Bangsa. A descriptive quantitative approach was used, involving a saturated sample of all active lecturers (N=sample size, if available). Data were collected via questionnaires using a Likert scale (1–5) and analyzed through descriptive and gap analyses. The findings reveal a significant gap in both competence (Average Gap: 1.05) and performance (Average Gap: 1.11), with critical weaknesses identified in communication, research, and scientific publication skills. However, the analysis also indicates a notably high motivation for training (Average Gap: 0.31). The most pressing training needs focus on mastering digital learning technology and enhancing research capacity. The study concludes that the institution must implement strategic, TNA-based programs and supportive policies to bridge these skill gaps and optimize the highly motivated workforce, thereby driving continuous improvement in academic quality.
Keywords: Training Needs Analysis (TNA); Employee Competency; Performance Improvement; Digital Learning Technology; Academic Publication